2020
DOI: 10.1261/rna.077537.120
|View full text |Cite
|
Sign up to set email alerts
|

Comparative patterns of modified nucleotides in individual tRNA species from a mesophilic and two thermophilic archaea

Abstract: To improve and complete our knowledge of archaeal tRNA modification patterns, we have identified and compared the modification pattern (type and location) in tRNAs of three very different archaeal species, Methanococcus maripaludis (a mesophilic methanogen), Pyrococcus furiosus (a hyperthermophile thermococcale), and Sulfolobus acidocaldarius (an acidophilic thermophilic sulfolobale). Most abundant isoacceptor tRNAs (79 in total) for each of the 20 amino acids were isolated by two-dimensional gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 90 publications
1
38
0
Order By: Relevance
“…Notice, the presence of m 1 A58 and/or m 1 I57 depends much on the archaeon considered and the type of tRNA analyzed (especially the nature of nucleotide-59, see below). For example, most tRNAs from halophilic Archaea such as Haloferax volcanii display m 1 I57 and unmodified A58 [ 27 , 28 ], while tRNAs of thermophilic and hyperthermophilic Archaea often display m 1 A58 and/or m 1 I57 [ 29 ] and references therein.…”
Section: Modified Nucleotides Within the T-loop And G18 Stabilize mentioning
confidence: 99%
See 2 more Smart Citations
“…Notice, the presence of m 1 A58 and/or m 1 I57 depends much on the archaeon considered and the type of tRNA analyzed (especially the nature of nucleotide-59, see below). For example, most tRNAs from halophilic Archaea such as Haloferax volcanii display m 1 I57 and unmodified A58 [ 27 , 28 ], while tRNAs of thermophilic and hyperthermophilic Archaea often display m 1 A58 and/or m 1 I57 [ 29 ] and references therein.…”
Section: Modified Nucleotides Within the T-loop And G18 Stabilize mentioning
confidence: 99%
“…In Archaea , while Gm18 has been experimentally identified in tRNA of different thermophilic organisms [ 29 ], no stand-alone homolog of TrmH/TRM3 has yet been identified. Instead, an alternative pathway involving a C/D box guide has been suggested, as in the case of 2′- O -ribose methylation of C56 of the T-loop (see below) and also for other nucleotides in the anticodon loop and position 50 of the T-arm [ 40 , 41 ].…”
Section: The Enzymatic Toolbox For Nucleotide Modifications At Posmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a tRNA-targeting sRNA can mediate methylation of either a single or many tRNAs, depending on whether its guide targets a unique sequence like the region surrounding the wobble base in the anticodon (position 34) or a conserved sequence shared across different tRNA families (Lui et al, 2018). Conversely, a few tRNAs in S. acidocaldarius and P. furiosus contain several methylated or predicted methylated nucleotides which have not yet been linked to corresponding sRNAs or stand-alone specific methyltransferases (Wolff et al, 2020). Several computational studies also identified numerous "orphan guides, " which are defined as snoRNA guide sequences that do not show complementary to any known RNA target (Hüttenhofer et al, 2001;Yang et al, 2006;Lui et al, 2018).…”
Section: Non-ribosomal Targetsmentioning
confidence: 99%
“…The distribution of nucleotide mismatch and RTa, respectively, can be used not only to identify modified sites but also to predict the identity of the modification; such a mismatch-based method is implemented in HAMR [11,15]. While this approach cannot provide unambiguous proof for the identity of a modification, it can be used as evidence in particular in comparative settings, e.g., when the identity of the modification at a homologous site in another species has been validated e.g., by mass spectrometry [34,35]. While approximately complete profiles of tRNA modifications are not available for most organisms, they are known for a limited number of eukaryotes including yeast, human, and rat [3].…”
Section: Introductionmentioning
confidence: 99%